Rapid early remission in a patient with severe aplastic anemia: a case report of hetrombopag, cyclosporine, and danazol combination therapy - Dai, Yuting; Guo, Qiang; Guo, Xiaoxiao; Liu, Qiuju (Frontiers in Immunology, 2025)
Severe aplastic anemia (SAA) is a life-threatening bone marrow failure syndrome that is caused primarily by immune-mediated destruction of hematopoietic stem cells. Traditional treatment relies on immunosuppressive therapy (IST) with antithymocyte globulin (ATG) and cyclosporine (CSA). However, the toxicity and limited availability of ATG have spurred interest in ATG-free regimens. This case report describes a 28-year-old male with SAA who was treated with a combination of CSA, danazol, and hetrombopag (HPAG). The patient presented with pancytopenia and a hypocellular bone marrow, thus meeting the SAA criteria. He received CSA (5 mg/kg/day), HPAG (started at 10 mg and increased to 15 mg/day), and danazol (400 mg/day). Hematologic assessments using the NIH criteria revealed a partial response at 3 months and a complete response at 6 months, with reduced proportions of active T-cell subclones and no severe adverse events. This case suggests that the combination of CSA, HPAG, and danazol is effective in treating SAA, and a large-scale clinical trial is warranted to further confirm these promising results.